2017
DOI: 10.1016/j.jalz.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms as risk factors of dementia in a Mexican population: A 10/66 Dementia Research Group study

Abstract: IntroductionCognitive and/or memory impairment are the main clinical markers currently used to identify subjects at risk of developing dementia. This study aimed to explore the relationship between the presence of neuropsychiatric symptoms and dementia incidence.MethodsWe analyzed the association between neuropsychiatric symptoms and incident dementia in a cohort of 1355 Mexican older adults from the general population over 3 years of follow-up, modeling cumulative incidence ratios using Poisson models.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 57 publications
4
44
0
Order By: Relevance
“…Dementia incidence in the current study was 30.7 cases per 1000 person-years. This is similar to a previous study reporting that dementia incidence was 32.5 cases per 1000 person-years in people over 65 years old from the general population [26]. Most patients developed AD in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Dementia incidence in the current study was 30.7 cases per 1000 person-years. This is similar to a previous study reporting that dementia incidence was 32.5 cases per 1000 person-years in people over 65 years old from the general population [26]. Most patients developed AD in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The few studies of anxiety as a risk factor for dementia have produced conflicting results. Several studies suggest that anxiety is a risk factor for dementia (8,9,14) while three other investigations estimate that dementia risk is increased by 48-70% in those with anxiety symptoms (11)(12)(13). However, de Bruijn et al (10) found no association of either anxiety symptoms or anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between anxiety and dementia has received recent attention (8)(9)(10)(11)(12)(13), but the nature of this relationship (true association or reverse causation) remains unclear. The few studies of anxiety as a risk factor for dementia have produced conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three months ago, some investigators documented the association between the presence of hallucinations, delusions, anxiety, depression, and abnormal motor behavior, with the risk of developing incident dementia, independent of other known risk factors, including MCI in the future, a simple, low-cost strategy for screening population groups at dementia risk, particularly in environments with limited access to specialized services and very sophisticated resources [37][38][39][40].…”
Section: Genetic Typesmentioning
confidence: 99%